Functional identification of hot-spot mutations in cardiac calcium channel genes associated with the J wave syndromes. (19th June 2023) - Zeng, Bin; Zhang, Xiang; Schimpf, Rainer; Powers, Andrew; Glikson, Michael; Antzelevitch, Charles; Hu, Dan; Barajas-Martinez, Hector
Abstract : J wave syndrome (JWS) is an inherited cardiac channelopathy associated with malignant ventricular arrhythmias and sudden cardiac death (SCD), which comprises early repolarization syndrome and Brugada syndrome. Here, we explore the association between variants in the L -type calcium channel gene subunits, α1C ( CACNA1C ) and β2b ( CACNB2b ), and the JWS phenotype. Using next-generation genetic sequencing of 402 JWS probands and their family members, we identified a CACNA1C -G37R (p.Gly37Arg) mutation in five individuals in four families, two of which had a family history of SCD as well as a CACNB2b -S143F (p.Ser143Phe) mutation in seven individuals in three families, two of which had a family history of SCD. The variants were located in exon 2 in CACNA1C and exon 5 in CACNB2b ; both were in highly conserved amino acid residues. Whole-cell patch-clamp results showed that compared with the wild-type group, calcium current density of CACNB2b- S143F and CACNA1C -G37R were significantly lower displaying a dominant-negative effect. Our findings provide further support for the hypothesis that variants in CACNA1C and CACNB2b are associated with JWS. The results suggest that mutations in these two genes lead to loss-of-function of the cardiac calcium channel current warranting their inclusion in genetic screening protocols. This article is part of the theme issue 'The heartbeat: its molecular basis and physiological mechanisms'.